Knowledge Management on PMO’s Perspective: A Systematic Review - Cunha, José Adson (2019)
Submitted by Domingos Martinho (domingos.martinho@islasantarem.pt) on 2019-07-03T00:32:45Z No. of bitstreams: 1 12-Knowledge_Management_on_PMOs_Perspective_Systematic_Review.pdf: 341825 bytes, checksum: e68f488ec793adb40e200c7f4d3b72e0 (MD5)